1) 2sin x - sin x=0 sin x = 0 x = πn, n∈Z 2) cos 2x cos 4x - sin 2x cos 4x = 1 cos (2x+4x) = 1 6x = πn x = πn/6, n∈Z 3) Если в таком виде, как написано, то: sinx - π/9 = 0 или cos3x + 6π/5 = 0 sinx = π/9 cos3x = -6π/5 x = (-1)^n*arcsin(π/9) + πn нет корней, т.к. 6π/5>1 А если (sin (x-π/9))(cos (3x + 6π/5))=0 sin (x-π/9) = 0 или cos (3x + 6π/5) = 0 ⇒ cos (3x + π + π/5) = 0 x-π/9 = πn - cos (3x + π/5) = 0 x = π/9 + πn 3x+π/5 = π/2 + πk 3x = π/2 - π/5 + πk 3x = 3π/10 + πk x = π/10 + (πk)/3
Пошаговое объяснение:
4a+7b=35.
4a=35-7b
Тут два варианта
4a=7(5-b) либо a=8.75 -1.75b
a=1.75(5-b)